HOW CAN A BINARY COMPUTER SIMULATE THE PROCESS OF REASONING? - Odescalchi, Edmond P. (Science Education, 1963)
The article focuses on the process of reasoning in a binary computer. Computer elements have only two natural states. It is a simpler way of calculation than the decimal mode. Binary symbols start with a 0 and end with a 1. Binary digits can be manipulated in a number of ways. Arithmetic operations are similar in both the decimal and the binary system. Most of digital computers perform their tasks in binary arithmetic. Subtraction is performed through addition of the ones complement. Division may be accomplished by repeated addition of the complement. The calculus of reasoning is essentially identical with the calculus of number. The apparatus designed to mechanize calculation is also able to simulate the process of logical reasoning because of the formal identity of the rules of the logical and arithmetic calculi in binary notation.